2008
DOI: 10.1007/s00497-008-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular repertoire of flowering plant male germ cells

Abstract: Sperm cells-the male gametes of flowering plants-constitute the male founding lineage of angiosperms, possessing the unique capacity to fuse with the egg and central cells during double fertilization. Although it is well established that these cellular fusions are involved with initiating the development of the seedling-forming zygote and the endosperm that nourishes it, considerable information will be needed to characterize the full male molecular repertoire, which includes expressed genes of the male lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…5 and Supplementary Table 2), which further confirms evolutionarily conservation of sperm cell genes across different plant species (Singh et al 2008). Thirty-five genes were found in the sperm cells of all three species, as shown in Supplementary Table 3.…”
Section: Examination Of Paternal Transcripts In Egg Cells and Zygotessupporting
confidence: 79%
See 1 more Smart Citation
“…5 and Supplementary Table 2), which further confirms evolutionarily conservation of sperm cell genes across different plant species (Singh et al 2008). Thirty-five genes were found in the sperm cells of all three species, as shown in Supplementary Table 3.…”
Section: Examination Of Paternal Transcripts In Egg Cells and Zygotessupporting
confidence: 79%
“…The authors presumed that maize sperm cDNA sequencing might help to identify mRNAs that were not detected in the Arabidopsis microarray analysis (Borges et al 2008). In addition, a high proportion of P. zeylanica sperm ESTs have no similarities with those in the NCBI database, suggesting that numerous genes related to sperm cell development are essentially unknown (reviewed by Singh et al 2008) and that genes involved in sperm specialization might vary significantly among species. Therefore, a specific cDNA library for a number of different model plants may be necessary, particularly for the purpose of screening for some regulators of male gametogenesis and gamete interaction during fertilization.…”
Section: Introductionmentioning
confidence: 97%
“…Transcriptomics approaches have identified a number of candidate plasma membrane localized proteins in sperm and egg cells of maize and Arabidopsis, respectively, (for review, see Dresselhaus 2006). Although we are still awaiting functional studies, a number of plant sperm and egg marker lines are now available (see also Singh et al 2008, this issue) that will aid to identify and characterize more key players of early and late fertilization events.…”
Section: Gamete Interaction and Fusionmentioning
confidence: 97%
“…Unlike the earliest seed plants, angiosperm sperm cells are not independently motile, but are believed to be conveyed by interactions of myosin with dynamic F-actin bundles located in largely isotropic orientation in pollen grains and axially within the sub-apical pollen tube (Hepler et al 2001). For much of the twentieth century flowering plant sperm cells were believed to consist of bare nuclei, but careful light microscopic observation (Maheshwari 1950) and electron microscopy indicated that sperm, despite their small size, contained organelles and displayed other normal cell functions including transcription, translation and unique gene expression (Singh et al 2008). The two male gametes also appear to be physically linked, as one sperm cell appears to be intrinsically associated with vegetative nucleus, whereas the other is linked to the first within a common inner pollen plasma membrane (Russell and Cass 1981), forming an assemblage known as the male germ unit (MGU) (Dumas et al 1984).…”
Section: Introductionmentioning
confidence: 98%